Penerapan Model Pembelajaran SAVI untuk Meningkatkan Keterampilan Membaca pada Pembelajaran Bahasa - Sanggar Pawesti Regita Ningrum; Nur Ismah; Zahrotul Farida; Yuliati Yuliati; Yadhi Nur Amin; Hananto Bangun Laksono (Kampus Akademik Publiser, 2025)
There are still many students who have difficulty in developing optimal reading skills, both in terms of speed and understanding of reading content. One of the learning models that is considered capable of fostering these abilities is the SAVI learning model. This study aims to describe the steps, advantages, and disadvantages of applying the SAVI learning model in language learning at MTsN 4 Klaten, MAN 2 Rembang, and MAN Sukoharjo. The research used a qualitative approach with the subject of Language teachers through interview, observation, and documentation techniques. The results showed that the steps of applying SAVI include: preparation by arousing interest and learning readiness; delivery of material by involving the five senses to suit the learning style of students; training to integrate and absorb new knowledge; display of results to help students apply and expand knowledge; and closing with joint reflection related to learning difficulties. The advantages of this model are that it generates integrated intelligence through combining physical and intellectual, creates an interesting learning atmosphere, enhances creativity and psychomotor skills, and maximizes concentration with visual, auditory and intellectual approaches. As for the weaknesses, this model requires teachers who are able to integrate the four SAVI components as a whole, requires adjustments according to conditions, and does not yet have assessment guidelines. In conclusion, the SAVI model can be applied to improve students' reading skills in madrasah.